Pengaruh Ketersediaan Barang, Efektivitas Komunikasi, dan Strategi Promosi terhadap Volume Penjualan PT.Distribusindo Cemerlang Jaya - Komariya Komariya; Maizar Maizar; Nurmayunita Nurmayunita (Jurnal Manajemen Riset Inovasi, 2026)
This study aims to determine the effect of product availability, communication effectiveness, and promotional strategy on sales volume at PT.Distribusindo Cemerlang Jaya, a cosmetic and skincare distribution company in Batam city. The background of this research is based on pre-survey result indicating suboptimal sales volume along with operational challenges including stock shortages, communicatiob gaps, and limited promotional activities.ths research employs a quantitative method. The population consist of all comsumers, with a sample of 43 respondent selected using a saturated sampling technique. Data were collected through questionnaires using a likert scale and analyzed using validity and reliability test, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination (R²) with SPSS. Result show that partially, product availability does not significantly affect sales volume (sig. 0,313 > 0,05), and communication effectiveness also does not significantly affect sales volume (sig. 0,898 > 0,05). However, promotional strategy has a positive and significant effect  on sales volume (sig, 0,000 < 0,05). Simultaneously, all three variables significantly affect sales volume (F = 212.642, sig. 0,000 < 0,05). The coefficient of determination (R²) is 0,942 indicating that 94,2% of the variation in sales volume is explained by the three independent variables. Promotional strategy is the most dominant factor influencing sales volume is explained by the three independent variables. Promotional strategy is the most dominant factor influencing sales volume at PT.Distribusindo Cemerlang Jaya.